Subject Librarians Vs Collection Data: How to Use Data to Visualize a Small Monograph Collection - Looby, Kimberly (Technical services quarterly, 2021)
To understand an Anthropology print collection, a librarian at an urban university created data visualizations. The librarian analyzed the Library of Congress Classification call numbers GN, publication decade, checkout rage, gender of author and title keywords for analysis. The analysis found an overemphasis of books in certain geographical areas, authors skewed male, and during the years 2013-2019 only 200 books were checked out and 75% of the collection was not checked out. The goals of the study are to visualize a print collection quickly, increase librarian confidence in using spreadsheets, and advocate for strong collection development.